Strategic Behaviour in International Metallurgical Coal Markets - Johannes Trüby (Institute of Energy Economics at the University of Cologne (EWI), 2012)
This paper analyses whether prices and trade-flows in the international market for metallurgical coals were subject to non-competitive conduct in the period 2008 to 2010. To do so, I develop mathematical programming models – a Stackelberg model, two varieties of a Cournot model, and a perfect competition model – for computing spatial equilibria in international resource markets. Results are analysed with various statistical measures to assess prediction accuracy of the models. The results show that real market equilibria cannot be reproduced with a competitive model. However, real market outcomes can be accurately simulated with the non-competitive models suggesting that market equilibria in the international metallurgical coal trade were subject to strategic behaviour of coal exporters.
Keywords: C61; L11; L13; L71; Q31; 330; metallurgical coal trade; market power; oligopoly; Stackelberg; Cournot